Study on key mechanical properties of the flexible spoke non-pneumatic tire considering thermo-mechanical coupling. (November 2022) - Fu, Hongxun; Liang, Xuemeng; Chen, Kai; Wang, Yan; Xiao, Zhen
Highlights: Based on the thermal mechanical sequential coupling method, the structural field and temperature field of the flexible spoke non-pneumatic tire are analyzed, and the thermal mechanical coupling analysis model is constructed by using the predefined field method. Considering the coupling effect of structural field and temperature field, the basic mechanical properties of the flexible spoke non-pneumatic tire are investigated, and the J-integral method is used to predict the fatigue life of the non-pneumatic tire. The key mechanical properties of the flexible spoke non-pneumatic tire considering thermal mechanical coupling are closer to the actual operating conditions. Abstract: Based on the combination of numerical analysis and prototype test, this paper explores the key mechanical properties of the flexible spoke non-pneumatic tire under thermo-mechanical coupling, mainly including basic mechanical properties and fatigue properties. Based on the thermo-mechanical sequential coupling method, the structural field and temperature field of the flexible spoke non-pneumatic tire is analyzed, and the thermo-mechanical coupling analysis model is constructed by using the predefined field method. Based on the thermo-mechanical coupling analysis model, the basic mechanical properties of the flexible spoke non-pneumatic tire are investigated, and the J-integral method is used to predict the fatigue life of the non-pneumatic tire. The results show that the vertical displacement, the grounding area, and the axial displacement in the rolling process with thermo-mechanical coupling are similar to those without thermo-mechanical coupling, but each of them increases; based on the J-integral method, the predicted fatigue failure mileage of non-pneumatic tire is 2.67 × 10 4 km, and the fatigue failure mileage of indoor drum test is 2.44 × 10 4 km, which is basically consistent. The key mechanical properties of the flexible spoke non-pneumatic tire considering thermo-mechanical coupling are closer to the actual operating conditions. The development of this paper has important theoretical significance and application value for the development of tire safety technology.